Analisis Pemakaian Bahasa Persuasif pada Konten Promosi UMKM dan Pengaruhnya terhadap Peningkatan Pendapatan pada UMKM Just Koling Afastar Coffee - Meilina Widya Dali; Silvana Sunge; Asrit I. Mohamad; Fathur Amruslim Samparaja; Alif Alfiansyah Hagu; Dwi Dytha Fathia Lobu; Trifina S. Katung; Sunyani Sunyani; Nur Fadilah Yahya; Nurul Fadilla Mopangga; Muniifa Hasan; Sania Fitri Talib; Rahmiyanti Abdul; Nazwa Fidya Gani; Firman Utina (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The rapid development of digital technology has encouraged micro, small, and medium enterprises (MSMEs) to utilize social media as an effective and efficient promotional medium. One important aspect of digital promotion is the use of persuasive language, which plays a key role in attracting attention and influencing consumer interest. This study aims to analyze the use of persuasive language in promotional content of the MSME Just Koling Afastar Coffee and to examine its role in increasing consumer interest and supporting business revenue growth. This research employed a descriptive qualitative method with documentary and field approaches. Data were collected through interviews with the owner and manager of the MSME, as well as documentation of promotional content published on social media platforms. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the promotional content of Just Koling Afastar Coffee is dominated by persuasive language in the form of short, casual, and easily understood invitation sentences. The use of persuasive language plays an important role in attracting consumer interest, increasing social media interaction, and supporting the growth in the number of customers and business revenue. This study confirms that persuasive language is a relevant and applicable marketing communication strategy for MSMEs, particularly in social media-based digital promotion.